Photoreceptor Disc Enclosure Occurs in the Absence of Normal Peripherin-2/rds Oligomerization - Lewis, Tylor R.; Makia, Mustafa S.; Kakakhel, Mashal; Al-Ubaidi, Muayyad R.; Arshavsky, Vadim Y.; Naash, Muna I. (Frontiers in Cellular Neuroscience, 2020)
Mutations in the peripherin-2 gene (PRPH2, also known as rds) cause a heterogeneous range of autosomal dominant retinal diseases. PRPH2 encodes a photoreceptor-specific tetraspanin protein, PRPH2, that is a main structural component of the photoreceptor outer segment. PRPH2 distributes to the rims of outer segment disc membranes as they undergo the process of disc membrane enclosure. Within these rims, PRPH2 exists in homo-oligomeric form or as a hetero-oligomer with another tetraspanin protein, ROM1. While complete loss of PRPH2 prevents photoreceptor outer segment formation, mutations affecting the state of its oligomerization, including C150S, C213Y and Y141C, produce outer segment structural defects. In this study, we addressed whether any of these mutations also affect disc enclosure. We employed recently developed methodology for ultrastructural analysis of the retina, involving tissue processing with tannic acid, to assess the status of disc enclosure in knockin mouse models bearing either one or two alleles of the C150S, C213Y and Y141C PRPH2 mutations. While varying degrees of outer segment structural abnormalities were observed in each of these mouse models, they contained both newly forming “open” discs and mature “enclosed” discs. These data demonstrate that normal PRPH2 oligomerization is not essential for photoreceptor disc enclosure.